Physical fitness assessment of women after 60 years of age - Prystupa Tetyana; Bolach Eugeniusz; Bolach Bartosz; Juliusz Migasiewicz; Paliga Zdzisław (Kharkov National Pedagogical University, 2012)
Introduction. Nowadays, progressive aging of society results in the need to address problems and needs of the elderly people. Aim of this study is to evaluate the physical and health conditions among women in the age group over60 years. Material and methods of research: the study was conducted in the focus group of women from University of the Third Age (UTW) and ASTW AWF Wroclaw. Average age in the focus group was 62 years. The study was conducted using the Fullerton Functional Fitness Test. As a part of the study, Body Mass Index (BMI) was calculated by measuring general anthropometric measurements. In addition, the study entailed an interview regarding practiced physical activity among women in the study group. They exercised 1 hour 3 times a week. Test results: The research revealed that women had similar somatic values, such as height and weight. The level of physical fitness in the focus group was in the range of healthy standards. Women from the AWF shown better results in terms of physical fitness in comparison to women from ASTW group, except for the upper body agility. Conclusions: The level of physical fitness for most of the women in both study groups was normal. The only exception was cardio-pulmonary endurance in a group of women from ASTW, where only 25% of participants exceeded the minimum expectation.